2013
DOI: 10.1177/1541204013485606
|View full text |Cite
|
Sign up to set email alerts
|

Differential Racial/Ethnic Predictive Validity

Abstract: Recent findings indicate that including White offenders in the sample biases the predictability of risk and needs assessment instruments. As a result, this study examines the predictability of the Los Angeles County Needs Assessment Instrument (LAC) on a sample of African American and Hispanic juvenile probationers. Given that the extant literature focuses on regression analysis, to the curtailment of error analysis, this study also provides a unique examination of predictive error. The results suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
3
17
1
Order By: Relevance
“…Other studies have defined bias as a difference in error classification or false positive rates, meaning a risk instrument may falsely classify one group as high risk at a higher rate than another group, which could easily result in unfair, harsher treatment of the group with more misclassifications. This approach was taken by a few non-peer-reviewed studies that reported a bias against Black adults (e.g., Angwin et al, 2016; Lason et al, 2016 [both were discredited, see Flores et al, 2016]), and a few peer-reviewed studies since 2000 (e.g., Muir et al, 2020; Rembert et al, 2014; Skeem & Lowenkamp, 2020), which found differences in false positive rates were small to nonsignificant or favored the particular group of color (meaning more individuals who were not categorized as high-risk recidivated), with one exception (see Dressel & Farid, 2018).…”
Section: What Does It Mean For An Instrument To Be Racially Biased?mentioning
confidence: 99%
“…Other studies have defined bias as a difference in error classification or false positive rates, meaning a risk instrument may falsely classify one group as high risk at a higher rate than another group, which could easily result in unfair, harsher treatment of the group with more misclassifications. This approach was taken by a few non-peer-reviewed studies that reported a bias against Black adults (e.g., Angwin et al, 2016; Lason et al, 2016 [both were discredited, see Flores et al, 2016]), and a few peer-reviewed studies since 2000 (e.g., Muir et al, 2020; Rembert et al, 2014; Skeem & Lowenkamp, 2020), which found differences in false positive rates were small to nonsignificant or favored the particular group of color (meaning more individuals who were not categorized as high-risk recidivated), with one exception (see Dressel & Farid, 2018).…”
Section: What Does It Mean For An Instrument To Be Racially Biased?mentioning
confidence: 99%
“…Rembert, Henderson, and Pirtle (2014) focused on the predictive error differences across 480 Black and Hispanic/Latino males utilizing the Los Angeles County Needs Assessment Instrument (LAC). Results indicate that overclassification errors were similar for the two groups across three different cutoff scores.…”
Section: Classification Errors and Risk Assessmentsmentioning
confidence: 99%
“…On one hand, numerous findings have demonstrated that of any racial/ethnic group, Black offenders had the greatest likelihood of being classified as high risk (Eisenburg, Bryle, & Fabelo, 2009;Henderson, 2006;Henderson, Daniel, Adams, & Rembert, 2007;Whiteacre, 2006;Yacus, 1998). Research has also demonstrated predictive bias with minority offenders being more likely to be overclassified (i.e., Type I error or false positive) (Rembert et al, 2014;Whiteacre, 2006). Findings additionally indicated a direct relationship between the number of Whites in the sample and the instruments' predictability (Edens, Campbell, & Weir, 2007;Gendreau, Goggin, & Little, 1996;Leistico, Salekin, DeCoster, & Rogers, 2008).…”
Section: Racementioning
confidence: 99%